2020
DOI: 10.1158/2326-6066.cir-19-0623
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the SRC Kinase HCK Impairs STAT3-Dependent Gastric Tumor Growth in Mice

Abstract: Persistent activation of the latent transcription factor STAT3 is observed in gastric tumor epithelial and immune cells and is associated with a poor patient prognosis. Although targeting STAT3-activating upstream kinases offers therapeutically viable targets with limited specificity, direct inhibition of STAT3 remains challenging. Here we provide functional evidence that myeloid-specific hematopoietic cell kinase (HCK) activity can drive STAT3-dependent epithelial tumor growth in mice and is associated with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…In the present study, HCK was demonstrated to be highly expressed in both tumor tissues from patients with GBM and GBM cell lines. Previous studies also reported excessive HCK expression in colorectal, breast, and gastric cancer [11][12][13]. Subsequently, we analyzed the effects of HCK on GBM development both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In the present study, HCK was demonstrated to be highly expressed in both tumor tissues from patients with GBM and GBM cell lines. Previous studies also reported excessive HCK expression in colorectal, breast, and gastric cancer [11][12][13]. Subsequently, we analyzed the effects of HCK on GBM development both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 89%
“…The HCK, a member of SFKs, is expressed in hematopoietic system, primarily including cells of the myeloid and B lymphocyte lineages [9,10]. Excessive activation of HCK is associated with various leukemia, such as CML, multiple myeloma, and acute lymphoblastic leukemia, as well as solid malignancies including colorectal, breast, and gastric cancer [11][12][13]. Nevertheless, the roles of HCK in GBM remain to be examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that, excessive activation of HCK is associated with various leukemias, such as chronic myelogenous leukemia (CML) and acute lymphoblastic leukemia, as well as solid malignancies including colorectal cancer, breast cancer and gastric cancer. In gastric tumor epithelial cells, over expression of HCK can induce alternative polarization of macrophages, activation of STAT3 and promote tumor growth [26]. Roseweir et al [27] reported that, HCK was highly expressed in patients with colorectal cancer, it could promote tumor progression, inhibit local lymphocyte in ammatory in ltration and are related to the poor prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%